Analisa Manajemen Operasional pada perusahaan PT. Lautan Lestari Shipyard - Rano Ardiansyah; Julius Kurnaedi; Jimmy Lim; Calvin; Julnando Lim (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The increase in the shipping industry in the city of Batam is increasingly developing and the emergence of many companies engaged in the same field giving rise to competitors, one of the most important factors within a company if it wants to survive and compete is the operational management of their company, operational management can help companies achieve company goals. The shipping companies studied were PT. Lautan Lestaro Shipyard, PT provides services for carrying goods nationally and internationally such as carrying sand, coal, gypsum seeds. During the Covid-19 pandemic, this PT did not experience a drastic economic decline because the company implemented a very good operational activity strategy for the company.